Self-Oriented and Socially Prescribed Perfectionism Among Hungarian Professional Folk Dancers - Csilla Almássy; Klára Soltész-Várhelyi; Anita R. Fedor (European Journal of Mental Health, 2025)
Introduction: Those characterized by high levels of self-oriented or socially prescribed perfectionism strive to meet high expectations. Dancers are prone to perfectionism and related negative psychological factors. Aims: In this study, we investigated how perfectionism among Hungarian professional folk dancers is related to certain psychological factors. Methods: Ninety-six professional dancers completed an online survey (47.9% male, 52.1% female, mean age: 29.91 years, SD = 8.46). To measure perfectionism, we utilized Hewitt and Flett’s Multidimensional Perfectionism Scale. We carried out a moderation analysis based on linear regression to measure the associations between the perfectionism subscales and various psychological variables and examine whether the two subscales moderated each other’s effects. Results: Higher levels of socially prescribed perfectionism were associated with higher perceived stress, burnout, weaker concentration, and lower coachability. On the other hand, self-oriented perfectionism showed fewer associations; however, these were indicative of a better mental state: those with higher self-oriented perfectionism showed lower levels of burnout, better concentration, and higher coachability. We also found that the two dimensions of perfectionism moderate each other’s effects. In the case of concentration and coachability, self-oriented perfectionism may mitigate the detrimental effects of socially prescribed perfectionism. In contrast, in the case of perceived stress, self-oriented perfectionism may actually exacerbate the harmful effects of socially prescribed perfectionism. Conclusions: The results showed significantly more dysfunctions associated with socially prescribed perfectionism. On the other hand, self-oriented perfectionism was associated with adaptive psychological outcomes.